Synthesis, characterization, curing, thermophysical and mechanical properties of ethylene dichloride-based polysulfide polymers. Issue 5 (9th April 2021) - Sheydaei, Milad; Talebi, Saeid; Salami-Kalajahi, Mehdi
Abstract: Good resistance to the solvent and excellent adhesion to many substrates are the significant features of polysulfide polymers. They are known to have extensive applications as sealants, adhesives and coatings. In this research, a series of polysulfide polymers of linear organic monomer (ethylene dichloride) and sodium-based aqueous monomers are synthesized using interfacial polymerization and zinc oxide (ZnO) is used as a curing agent. The curing process of the synthesized polymers is studied using a rheometer at 160 °C. The cured and uncured samples are characterized by Fourier-transform infrared, Raman, XRD, DSC, Shore A and tensile tests. XRD results showed that cured samples possessed complete amorphous behavior whereas in the non-cured samples the structure shifts to the amorphous phase by increasing the sulfur content. The study of mechanical properties showed that with increasing sulfur content, the elastic modulus and elongation at break were increased. Furthermore, the glass transition temperature and crosslinking density were increased with increasing sulfur content whereas hardness was decreased. Besides, Thermogravimetric analysis results showed that in the cured samples the thermal stability was increased with increasing sulfur content. Also, all samples were resistant to benzine, gasoline, white spirit, engine oil and brake-fluid. Graphical abstract: